Transatlantic Air Travel in the Third Trimester of Pregnancy: Does It Affect the Fetus? - B. Petrikovsky; M. Terrani; L. Sichinava (Thieme Medical Publishers, Inc., 2018)
Most commercial airlines allow pregnant women to fly up to 36 weeks of gestation. Available information suggests that noise, vibration, and cosmic radiation present a small risk for the pregnant air traveler. The goal of the study was to assess the possible effect of transatlantic flights on the condition of the third-trimester fetus. In total, 112 patients were recruited into the study between January 2005 and June 2016. All underwent a transatlantic flight in the third trimester of pregnancy. All underwent nonstress test before and within 12 hours after the transatlantic flight, and 24 hours later. Patients were asked to report changes in fetal movements (FMs), if any, during takeoff, flight itself, and landing. The time of flight varied from 8 to 15 hours; average flight time was 9 ± 3.8 hours. Ninety-eight patients were the passengers of first or business class, and the rest were of economy class. Increased FM during takeoff was reported by 17 patients (15%), no change in FM by 62 (35%), decreased FM by 4 (3.6%). During flight itself, increased FM was reported by 6 pregnant passengers (5.4%), no change in FM by 70 (63%), decreased FM by 8 (7%).